Pengaruh Metode Ekstraksi Maceration Vortex Technique terhadap Total Flavonoid Content dari Daun Meniran (Phyllanthus niruri L.) - Miftahul Rahmi; Hesty Parbuntari (MASALIQ, 2025)
Phyllanthus niruri L., a medicinal plant from the Phyllanthaceae family, is widely recognized in traditional medicine for its flavonoid content in the leaves, which functions as a natural antioxidant protecting cells from damage caused by free radicals. This study aims to investigate the effect of the Maceration Vortex Technique (MVT) on the total flavonoid content of Phyllanthus niruri leaves. The method involved a 2-hour maceration process followed by 5 minutes of vortexing using 70% ethanol as the solvent. Total flavonoid content was analyzed using UV-Vis spectrophotometry at a maximum wavelength of 431 nm. The results demonstrated that the MVT method yielded a high flavonoid content, indicating the technique's effectiveness in extracting flavonoid compounds from Phyllanthus niruri leaves. The study concludes that MVT is a promising alternative extraction method that is efficient, simple, and applicable for obtaining bioactive compounds from natural sources. These findings have positive implications for the development of antioxidant-rich herbal products derived from natural ingredients.